Pengaruh Pemberian Perasan Jantung Pisang Kepok (Musa Paradisiaca Normalis) Terhadap Penurunan Kadar Glukosa Darah Mencit (Mus Musculus) Hiperglikemik Dan Implementasinya Sebagai Bahan Penyuluhan Gizi Kepada Masyarakat - Nur Hamidatul Badriyah; Abdul Ghoni (PEDAGO BIOLOGI, 2017)
Abstract : The problem in this study is Diabetes Mellitus which is a metabolic disease characterized by elevated levels of glucose in blood plasma. Complications of this disease can spread throughout the body, so the disease is called The Silent Killer. This study aims to analyze the effect of giving the distillation of heart of banana kepok (Moses paradisiacal normalize) to the decreasing of blood glucose level of hyperglycemic mice and its implementation as nutrition counseling to society. This Research Using experimental method with pretest - posttest Control Group Design. The samples were 9 mice for control group, 9 mice for treatment group 25% and 9 mice for treatment group 50%. The data obtained from the research data obtained Ï = 0.00, so Ï <Î± = 0.05, this means (Ha) received, so there is an effect of giving the banana heart juice to the decrease of blood glucose significantly. From the results of this study can be concluded that there is influence of distillation of banana kepok heart (Moses paradisiacal normalize) indecreasing blood glucose levels of hyperglycemic mice and Implementation as nutrition counseling materials to the community.